ANALYSIS OF INCOME LEVELS AND WELFARE OF SMALL-SCALE FISHERMEN'S HOUSEHOLDS IN BENGKULU CITY - Sudarma, Rahmat; Cahyadinata, Indra; Mulyasari, Gita; Supriyadi, Supriyadi (Jurnal Perikanan Unram, 2025)
According to data from BPS (2023), the capture fisheries production in Bengkulu City reached 41,919 tons in 2022. Despite its significant potential, fishermen’s income levels are highly dependent on unpredictable, uneven, and difficult-to-forecast catch results, often leading to their classification as "the poorest of the poor." This study aims to examine the income and welfare of small-scale fishing households in Bengkulu City, a region with substantial capture fisheries potential. Although the city recorded a production volume of 41,919 tons in 2022, many fishermen in this area continue to face challenges related to low welfare levels. Using welfare indicators from the National Population and Family Planning Board (BKKBN), this study analyzes the income and welfare levels of fishing households and explores the relationship between them. Primary data were collected through direct interviews and questionnaires, with small-scale fishermen selected using accidental sampling. Data analysis was conducted using the Chi-square test to determine the correlation between income and welfare. The findings indicate that the average monthly income of small-scale fishing households is IDR 2,130,553. The welfare levels of these households are categorized into three groups: Sejahtera II (26%), Sejahtera III (49%), and Sejahtera III Plus (25%). The Chi-square test results show a significance value of 0.010, indicating a significant relationship between income and fishermen’s household welfare. These findings suggest that income is the primary factor influencing the welfare of small-scale fishermen. Increasing income levels can serve as a strategic approach to improving the quality of life for fishermen and their families